INFRASONIC EFFECT OF SOLAR ECLIPSES - Pushin, V. F.; Chernogor, L. F. (Видавничий дім «Академперіодика», 2013)
The relevance of this study is due to the need to understandphysical effects associated with rare phenomenon, solar eclipse.Until recently, the features of internal gravity wave generationhave been studied in the 10 −100 min period range, while in thisstudy an attempt is made to confirm the fact of generationand estimate the general parameters of infrasound oscillationsassociated with solar eclipses in the 1−10 min period range.The observations were made with the HF Doppler radar at verticalincidence. The data were subjected to spectral analysis andband-pass filtering. The solar eclipses that had occurred overKharkiv city (Ukraine) within 1999–2011 are determined to beassociated with Doppler shift of frequency oscillations in theinfrasound frequency band (~ 5−8 min period range) and withamplitude of 20 −100 mHz. The corresponding amplitudeof electron density oscillations was approximately equal to0.1− 0.5 %.